Research of Surface Residual Stress Strengthening with Rolling for Anti-roll Torsion Bar - ZOU Min-jia; LIU Wen-song; GUO Chun-jie; NIE Qing-ming; LUO Bin (机车电传动)
Residual stress field of torsion bar after rolling was quantitatively measured with X-ray diffraction method. Test results showed that the measured method had accuracy data, small divergence factor, which could fulfill the requirement of residual stress in EN15049. Along with increase of rolling amount of feed, surface residual stress of torsion bar became bigger gradually, which was index distribution, and along with the further increase of amount of feed, increase trend of stress receded .